Interspecies comparison of sea star adhesive proteins. (9th September 2019) - Lengerer, Birgit; Algrain, Morgane; Lefevre, Mathilde; Delroisse, Jérôme; Hennebert, Elise; Flammang, Patrick
Abstract : Sea stars use adhesive secretions to attach their numerous tube feet strongly and temporarily to diverse surfaces. After detachment of the tube feet, the adhesive material stays bound to the substrate as so-called 'footprints'. In the common sea star species Asterias rubens, the adhesive material has been studied extensively and the first sea star footprint protein (Sfp1) has been characterized. We identified Sfp1-like sequences in 17 additional sea star species, representing different taxa and tube foot morphologies, and analysed the evolutionary conservation of this protein. In A. rubens, we confirmed the expression of 34 footprint proteins in the tube foot adhesive epidermis, with 22 being exclusively expressed in secretory cells of the adhesive epidermis and 12 showing an additional expression in the stem epidermis. The sequences were used for BLAST searches in seven asteroid transcriptomes providing a first insight in the conservation of footprint proteins among sea stars. Our results highlighted a high conservation of the large proteins making up the structural core of the footprints, whereas smaller, potential surface-binding proteins might be more variable among sea star species. This article is part of the theme issue 'Transdisciplinary approaches to the study of adhesion and adhesives in biological systems'.